The global threat of antimicrobial resistance: science for intervention. (July 2015) - Roca, I.; Akova, M.; Baquero, F.; Carlet, J.; Cavaleri, M.; Coenen, S.; Cohen, J.; Findlay, D.; Gyssens, I.; Heure, O.E.; Kahlmeter, G.; Kruse, H.; et al.
Abstract: In the last decade we have witnessed a dramatic increase in the proportion and absolute number of bacterial pathogens resistant to multiple antibacterial agents. Multidrug-resistant bacteria are currently considered as an emergent global disease and a major public health problem. The B-Debate meeting brought together renowned experts representing the main stakeholders (i.e. policy makers, public health authorities, regulatory agencies, pharmaceutical companies and the scientific community at large) to review the global threat of antibiotic resistance and come up with a coordinated set of strategies to fight antimicrobial resistance in a multifaceted approach. We summarize the views of the B-Debate participants regarding the current situation of antimicrobial resistance in animals and the food chain, within the community and the healthcare setting as well as the role of the environment and the development of novel diagnostic and therapeutic strategies, providing expert recommendations to tackle the global threat of antimicrobial resistance.